Study of Cement-sand brick Using Bamboo Ash in Term of Strength - Mohd Saip, Muhammad Amirul Rasyid; Suraya Hani Adnan (Progress in Engineering Application and Technology, 2022)
The growth of the building business generates a lot of construction trash, which causes social and environmental issues in communities [1]. This can be conclude that the most unwanted waste is concrete and aggregate which it cannot be reusable and difficult to dispose. Therefore, the researcher suggest the used of bamboo as cement partial replacement. As a result, in this study, researcher use bamboo as a building material to create eco-friendly building materials. This study focus on using bamboo ash materials and cement which to make concrete brick. A few test conducted as to test the chemistry composition of the sample, X-Ray fluorescence, Particle Size Analyser (PSA), Compressive Strength Test and Ultrasonic Pulse Velocity (UPV). The goals of this study is to determine compressive strength of concrete brick which content of bamboo ash, to investigate the quality of concrete bricks materials and to determine the bamboo ash is able to replace cement in concrete. This study contribute the reduction of cement usage able to minimize the concrete waste at landfill that is difficult to dispose and non-reusable. This research also helped to the development of a bamboo ash-based alternative to cement.